2017
DOI: 10.5858/arpa.2017-0099-oa
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Patients With Resected Tumor Deposit–Positive Colorectal Cancer: A Surveillance, Epidemiology, and End Results–Based Population Study

Abstract: - Radiotherapy did not independently improve OS among TD-positive CRC patients. In this study, classifying TD positivity as N1c was associated with worse OS than classifying TD positivity as N0. The findings seem to challenge the benefits of radiotherapy and the new N1c classification of TD for TD-positive CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In our previous study (32), we identified the survival benefit of postoperative RT for patients with pT3N0 disease in the high-risk subgroup. Nonetheless, it remains controversial whether all TDpositive patients should receive postoperative RT (33). In the current study, we also found that postoperative RT could only prolong the median OS of patients in the high-risk subgroup, but not in the low-risk subgroup.…”
Section: Discussionsupporting
confidence: 50%
“…In our previous study (32), we identified the survival benefit of postoperative RT for patients with pT3N0 disease in the high-risk subgroup. Nonetheless, it remains controversial whether all TDpositive patients should receive postoperative RT (33). In the current study, we also found that postoperative RT could only prolong the median OS of patients in the high-risk subgroup, but not in the low-risk subgroup.…”
Section: Discussionsupporting
confidence: 50%
“…We obtained individual-level data from the Surveillance, Epidemiology, and End Results-18 (SEER-18) (www.seer.cancer.gov) SEER*Stat Database with Treatment Data using SEER*Stat software (Surveillance Research Program, National Cancer Institute SEER*Stat software (seer.cancer.gov/seerstat) version <8.3.6>) as we did before [13][14][15]. SEER-18 is the largest SEER database including cases from 18 states and covering near 30% of the U.S. population.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, the authors suggest that the presence of TDs should be considered when implementing adjuvant treatment regimens and protocols. Chavali et al27 suggest that adjuvant radiotherapy improves prognosis for patients with TDs who did not receive neoadjuvant radiotherapy.…”
mentioning
confidence: 99%